Evaluation and Characterization of The Quantitative and Qualitative Traits in The Second Mutant Generation of Barley Variety Furat9 - Azzam, Hasan; ALek , Waled; Eskan , Mhmoud (Latakia University Journal -Biological Sciences Series, 2013)
The response of barley variety Furat9 (tow-rowed), has been noted for three doses of Gamma radiation (10, 15, and 20 Kr). The objective of the research, to evaluate and characterize the quantitative and qualitative traits, to identify and calculate the proportion of the total and relative changes, to determine the best doses of Gamma rays, and to study the relationship among the traits in the second generation. This research experiment was conducted in the growing season 2011-2012 at GCSAR- Karahta research station, The seed M2 mutants of Furat9 was planted using randomized complete block design with three replications in (RCBD) Statistical analysis revealed that the average ratio of total changes, caused by radiation treatment (6.02%), and many of The qualitative changes (9 types), these changes included total and relative sterility, wavy awns, early and late heading, color mutations, erect plant, long and wide spike, wide leaf . The different doses of Gamma radiation preformed significantly better in all the studied quantitative traits as compared to the control. The dose of 20 kilo Rads were shown The highest means of traits: number of fertile tillers per plant, Grain number and weight per plant, Thousand kernel weight, and biological yield, as compared to the other treatments, and almost all the correlation results were positive and significant between the studied traits.